2010
DOI: 10.1111/j.1556-4029.2010.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Fracture Characteristics of Rigid and Compliant Surface Impacts on the Infant Skull—A Porcine Model*,†

Abstract: This study documents skull fracture characteristics on infant porcine specimens under known impact conditions with respect to age and interface. A single impact causing fracture was conducted on the skull of porcine specimens aged 2-28 days (n = 76). Paired rigid and compliant impacts at the same energy were conducted at each specimen age. Impact force, impact duration, and fracture length were recorded. Energy required to initiate skull fracture increased with specimen age. For a given energy, impact of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
4
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 22 publications
3
69
4
2
Order By: Relevance
“…Porcine bone is believed to be a suitable human bone substitute in fracture research and has been used as a model in many forensic studies [3,[15][16][17]34,35]. Isolated porcine heads were used in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine bone is believed to be a suitable human bone substitute in fracture research and has been used as a model in many forensic studies [3,[15][16][17]34,35]. Isolated porcine heads were used in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Those studies which have investigated lateral impact biomechanics have utilised a variety of different methodologies including: static compression tests [11] (as cited in [7]), drop tests [3,[12][13][14][15][16][17], free fall tests [18][19][20], impacts with a pneumatic/ hydraulic piston [21,22], gas gun tests [23,24] and pendulum set ups [25]. Specimens utilised in these tests have also varied greatly, comprising of intact human cadavers, intact cadaver heads, dry human skulls and porcine specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Further, both the experimental and the simulated impact surface area suggest an overall increase with age, which is consistent with animal drop tests using infant porcine specimens (Baumer et al. 2010). …”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with experimental findings using infant porcine skull, where fractures initiated at bone–suture interfaces (Baumer et al. 2010). While in the studies using human PMHS by Weber (1984, 1985) only the fracture patterns were depicted and no discussion on the initiation of fractures was provided.…”
Section: Discussionmentioning
confidence: 99%
“…In their experimental study of the fracture process in young pigs aged 2-28 days, Baumer et al [84] explored factors of age as well as surface characteristics of the impacting object. They found that the energy required to initiate a fracture increased with increasing age.…”
Section: Recent Researchmentioning
confidence: 99%